2017
DOI: 10.6002/ect.2016.0027
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Objectives: Kidney transplant is a new area for use of rituximab, which is being used to treat acute antibodymediated rejection or as an induction agent in ABOor HLA-incompatible grafts. We report on late-onset neutropenia in rituximab-treated kidney transplant recipients with antibody-mediated rejection. Conclusions: Increased use of rituximab to treat antibody-mediated rejection among kidney transplant recipients requires attention to its late-onset adverse event, neutropenia. Although asymptomatic in some p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…A randomized double-blind, placebo-controlled study of efficacy and safety of rituximab induction in KTR found no thrombocytopenia in rituximab arm [ 42 ]. Likewise in another prospective observational case control study, thrombocytopenia was not seen in KTR receiving rituximab [ 43 ]. However, some noncontrolled studies have reported thrombocytopenia in KTR who received rituximab [ 44 , 45 ].…”
Section: Insight Into Etiology Of Hematological Cytopenia and Subsmentioning
confidence: 90%
See 1 more Smart Citation
“…A randomized double-blind, placebo-controlled study of efficacy and safety of rituximab induction in KTR found no thrombocytopenia in rituximab arm [ 42 ]. Likewise in another prospective observational case control study, thrombocytopenia was not seen in KTR receiving rituximab [ 43 ]. However, some noncontrolled studies have reported thrombocytopenia in KTR who received rituximab [ 44 , 45 ].…”
Section: Insight Into Etiology Of Hematological Cytopenia and Subsmentioning
confidence: 90%
“…LON has frequently been reported in KTR [ 44 , 45 , 56 59 ].The frequency of late-onset neutropenia in KTR has been reported from 37.5% to 48% in various studies [ 44 , 45 , 55 , 56 ]. Common medications incriminated in causing LON include mycophenolate mofetil or anti CMV medications (ganciclovir / valganciclovir).Ahmadi F et al [ 43 ] reported a high incidence (66.7%) of late-onset neutropenia [defined as neutropenia that occurred about 4 weeks after the last administered dose of rituximab without any other alternate explanation (e.g., unresponsive to dose reduction/cessation of ganciclovir/ valganciclovir, or mycophenolate mofetil)].…”
Section: Insight Into Etiology Of Hematological Cytopenia and Subsmentioning
confidence: 99%
“…R-LON is frequently reported in patients with B-cell lymphoma but has also been reported in cases of rheumatoid arthritis, systemic lupus erythematosus [9], overlap syndrome [8], renal transplantation [5, 7] and antineutrophil cytoplasmic antibody- (ANCA-) associated vasculitis [6]. The incidence is 3%-27% in B-cell lymphoma [11], 1.3%-2.3% in rheumatoid arthritis and autoimmune diseases [9], and 42%-70% in autologous stem cell transplantation [7]. The wide range of incidences is attributable to the diversity in patient backgrounds and treatments, inconsistent definitions of R-LON in the literature, and differences in the frequency of post-RTX administration blood sampling.…”
Section: Discussionmentioning
confidence: 99%
“…Although R-LON is generally asymptomatic and is known to spontaneously go into remission, reported cases of complicating infection that requires G-CSF or antibiotic treatment also exist [5, 6, 911, 13]. Deaths have also occurred due to severe infection [7, 19]. Caution is thus required to prevent R-LON onset.…”
Section: Discussionmentioning
confidence: 99%
“…Outside the context of oncology, biotherapies have been reported as being the cause of early and transient Grade 1–2 neutropenia in 10–15% of the treated patients, often with TNF-α inhibitors [16,19,20,21,22,23,24], tocilizumab [25,26,27], rituximab [14,27,28,29,30,31,32,33,34,35,36], and alemtuzumab [15,37,38,39,40,41,42]. In a retrospective cohort study involving 499 patients with rheumatic diseases (rheumatoid arthritis in 72% of the diseases) treated by intravenous abatacept, infliximab, or tocilizumab, Espinoza et al report at least one neutropenic episode in 52 patients (10.4%) [26].…”
Section: Epidemiological Datamentioning
confidence: 99%